Vloga naprednih tehnologij v inženiringu poslovnih sistemov - Mežnar, Dušan; Roblek, Matjaž; Hočevar, Timotej; Krhač Andrašec, Eva; Kern, Tomaž; Debeljak, Žiga; Maletič, Matjaž; Maletič, Damjan; Balantič, Zvone; Đoković, Sofija; Jarc Kovačič, Branka; Todorović, Petar; et al. (University of Maribor Press, 2025)
The Role of Advanced Technologies in Enterprise Engineering. Business systems are constantly confronted with the permanent need to make organizational changes in order to remain efficient, successful, and competitive in a changing business environment. One of the possible ways is the use of advanced technologies developed to utilize a large amount of available data to facilitate the work and improve the operations of business systems. For this purpose, the authors present the basics of various advanced technologies in their chapters. Based on literature reviews and research conducted, the reader is introduced to the possibilities of the practical use of advanced technologies in various business systems. In their chapters, the authors discuss the potential and current challenges of using advanced technologies. Authors classify the key success indicators of advanced technologies as leadership, comprehensive strategy, organizational structure and culture, cooperation of all stakeholders, and willingness to learn and adopt best practices. Only with a good understanding of the potential of advanced technologies and by closely following the application guidelines advanced technology can be expected to succeed in improving business systems.